(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2022)
Pulmonary tuberculosis is the major cause of morbidity and mortality in the developing world. In South Asia, 80% of the apparently healthy population have vitamin D deficiency (<20 ng/mL). An association between vitamin D levels with tuberculosis has been described in several studies. But there are scarcities of studies carried out in Bangladesh to determine the association. This study, a case-control study with 2 years duration, determined and compared vitamin D concentration between pulmonary tuberculosis patients and healthy controls. Patients were recruited from the department of internal medicine, Bangabandhu Sheikh Mujib Medical University. All newly diagnosed patients of pulmonary tuberculosis who fulfiled the inclusion and exclusion criteria were selected as case; equal number of healthy subjects without pulmonary TB as control. Vitamin D level less than 20 ng/ml was considered deficiency; 21 to 29ng/ml as relative insufficiency and >30ng/ml as normal. Thirty partici- pants in each group were enrolled, from whom serum vitamin D concentration was measured, analyzed and interpreted. Mean serum vitamin D level was significantly low in case group than control group (p <0.05). The odds ratio corresponding to vitamin D deficiency in case group compared to control was 5.21 [95% CI (1.12 –27.53), (p= 0.015)]. Result indicates patients having vitamin D level <20 ng/ml has 5.21 times more risk to develop pulmonary tuberculo- sis. In conclusion, Vitamin D deficiency was significantly low in pulmonary tuberculo- sis patients and supplementation is required for them. BSMMU J 2021; 14(3): 85-91